2011
DOI: 10.1111/j.1469-8986.2011.01300.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical exercise performed before bedtime improves the sleep pattern of healthy young good sleepers

Abstract: To investigate the influence of different intensities and durations of exercise before bedtime on the sleep pattern and core body temperature of individuals considered good sleepers, we selected 17 healthy males and all underwent 5 nonconsecutive days of study. Measurements of polysomnographic parameters and core body temperature were taken at baseline and after each experimental protocol, performed at night. We found increased sleep efficiency (p = .016) among all protocols compared with baseline data and inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(100 citation statements)
references
References 54 publications
5
90
1
4
Order By: Relevance
“…Entre elas podemos destacar o aumento do sono de ondas lentas [20][21][22][23] , aumento da latência para o sono REM 22,24 e a redução da latência para o início do sono quando não há alteração recuperação pode não haver alterações nestas variáveis 2,23,25,26 . Os resultados do presente estudo demonstraram que os atletas com uma pobre qualidade do sono apresentaram um aumento na latência do sono, sugerindo mais uma vez que fatores extrínsecos (como por exemplo, relação entre intensidade do treinamento e períodos de recuperação) ou intrínsecos (como por exemplo, distúrbios do sono) talvez estejam influenciando nessa má qualidade do sono.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Entre elas podemos destacar o aumento do sono de ondas lentas [20][21][22][23] , aumento da latência para o sono REM 22,24 e a redução da latência para o início do sono quando não há alteração recuperação pode não haver alterações nestas variáveis 2,23,25,26 . Os resultados do presente estudo demonstraram que os atletas com uma pobre qualidade do sono apresentaram um aumento na latência do sono, sugerindo mais uma vez que fatores extrínsecos (como por exemplo, relação entre intensidade do treinamento e períodos de recuperação) ou intrínsecos (como por exemplo, distúrbios do sono) talvez estejam influenciando nessa má qualidade do sono.…”
Section: Resultsunclassified
“…A relação entre o sono e o exercício físico pode sofrer influência de fatores como nível de aptidão física inicial, intensidade, duração do tempo e o tipo de exercício físico realizado 1,2 . Estudos demonstram que as contrações musculares exigidas na execução de qualquer exercício físico são estímulos capazes de promover depleção dos estoques de energia e provocar micro-lesões, ou seja, uma alta atividade catabólica durante a vigília que exige uma alta atividade anabólica durante o sono, em especial, durante o sono de ondas lentas (SOL) onde ocorre a maior liberação de hormônio do crescimento (GH) em especial em um terço da noite de sono 3,4 .…”
Section: Introductionunclassified
“…It is suggested that exercise accelerates the normal rate of decline of body temperature prior to sleep onset, leading to improved sleep quality and deeper sleep [146]. However, this hypothesis is challenged by Flausino and colleagues [101]; in their study, they examined the influence varying exercise intensities and durations 2-3 h before bedtime on sleep patterns and body temperature amongst good sleepers. The exercise conditions caused significant improvements in sleep efficiency and lowered WASO despite there being no differences in core temperature after exercise.…”
Section: Thermoregulationmentioning
confidence: 99%
“…Epidemiological studies also consistently show that exercise is associated with improved sleep quality [97][98][99][100]. Additionally, several studies account that partaking in regular physical activity is associated with a reduced risk of sleep disturbances and better sleep quality in adults [101]. The body of evidence suggests that vigorous exercise increases total sleep times by reducing sleep onset latency (SOL) and waketime after sleep onset (WASO) [18,102,103].…”
Section: Effects Of Exercise On Sleepmentioning
confidence: 99%
“…The relationship between body temperature regulation and sleep has been studied in depth 13) . In research on humans, there have been several studies which measured core body temperature during sleep after bouts of exercise, with a variety of inconsistent results ranging from no change 14) , to body temperature elevation 15,16) . A theoretical basis for sleep enhancement by body temperature elevation has been proffered by the hypothesis that SWS, which is associated with effects that reduce body temperature, might be promoted by a higher body temperature before bedtime 17) .…”
Section: Effect Of Exercise On Cns Sleepmentioning
confidence: 99%